Root cause failure analysis of reducer weld-joint leakage for liquid outlet of slug catcher. (February 2019) - Gurning, R A T; Priadi, D; Ferdian, D; Suryadi
Abstract: This paper presents a failure analysis of reducer weld-joint leakage for liquid outlet of slug catcher. The leak point was found on the area of weld joint with position relative to clock position from 9 to 3 o'clock. In order to determine morphology and mechanisms of crack were observed through laboratory tests including chemical composition test, weld macro analysis, microstructure analysis, and corrosion product analysis. Failure analysis result was found that corrosion process consumed the root weld material and cause leakage. The corrosion is occurred due to combination effect of galvanic cell, root weld microstructure, turbulence and corrosive fluids. Scaling was found based on scale analysis. Therefore the pH was indicated high enough and showed the small chance for corrosion due to carbon dioxide (CO2 ). Detailed investigation also revealed that the inconsistent of weld root which resulting excessive root penetration over 3 mm. An excessive weld root about 5.6 mm is observed which was as result of improper instant repair. This profile of weld root will disrupt the flow and cause the weld root to be more anodic and vulnerable to corrosion.